2018
DOI: 10.3390/ijerph15091965
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Allergies and Psychiatric Disorders in the United States

Abstract: Seasonal allergies have been associated with mental health problems, though the evidence is still emergent, particularly in the United States. We analyzed data from the National Comorbidity Survey Replication and the National Latino and Asian American Survey (years 2001–2003). Multivariable logistic regression models were used to examine the relations between lifetime allergies and lifetime psychiatric disorders (each disorder in a separate model), adjusting for socio-demographic variables (including region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies were conducted in America (19)(20)(21)(24)(25)(26)(27)29,35,36,41) , 7 in Europe (18,28,32,33,37,38,40) and 5 in Asia (22,23,30,31,39) . Thirteen studies included only adults (18,20,21,(27)(28)(29)(30)33,(35)(36)(37)(39)(40)(41) , 6 included only children/adolescents (19,22,23,26,31,34) and 4 included participants of both age groups (24,25,32,38) . Allergic rhinitis diagnosis was performed by a physician at the time of assessment in 6 studies (18)(19)(20)…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Allergy and psychological stress are related (Dave et al, 2011). Combined data from two household surveys in the USA (n = 10,334) suggests that lifetime seasonal allergies are associated with mood disorders (OR = 1.45; 95% CI 1.26-1.67) and anxiety disorders (OR = 1.60; 95% CI 1.42-1.78) (Oh et al, 2018). A study of 1,673 adolescents in Taiwan showed that adolescents with allergic rhinitis had increased hazard ratios for major depression (HR 1.59; 95% CI 1.02-2.50) (Chen et al, 2013).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Allergic rhinitis reduces quality of life, school and work performance [24]. There are reports, which show relation between allergic rhinitis and mood disorders, anxiety disorders and suicidal ideation [25]. Other than impact of symptoms on the somatic and mental spheres, the economic effects are significant.…”
Section: Allergic Rhinitismentioning
confidence: 99%